Social Discontent or Criminality? Navigating the Nexus Between Urban Riots and Criminal Activities in Gauteng and KwaZulu-Natal Provinces, South Africa (2021) - Mongale, Collin Olebogeng (Frontiers in Sustainable Cities, 2022)
The post-apartheid South Africa is characterized by the proliferation of public protests which occurs in various contexts. This includes urban riots that are typically carried out by individuals who live in residential areas that are relatively marginalized politically, socially, and economically. In this perspective, the paper seeks to navigate the nexus between urban riots and criminal activities in Gauteng and KwaZulu-Natal provinces of South Africa. This will be done through looking at the recent urban violence that erupted in Johannesburg and Durban cities of South Africa, following the arrest of the former president of South Africa Jacob Zuma on 7 July for contempt of court. As a result of the incarceration of Zuma, his supporters took to the streets to demand for his release, ending in protests which quickly evolved into widespread lootings, vandalism and an outbreak of violence which denoted elements of criminality. The two provinces Gauteng (the country’s economic hub) and KwaZulu-Natal (on the east coast) bore the brunt of this violence. What began as the call for the release of Jacob Zuma transpired into something that is heavily coordinated, controlled and to a larger extent, a dangerous and perhaps the worst post-apartheid urban riot. However, behind these riots, there are seeds of discontents which triggered these violent riots and these includes: the frustrations of hungry and cold people whose prospects were already constrained by the Covid-19 pandemic, rising inequality between rich and poor, unemployment, intra-party tensions and ANC-factionalism, including stereotypical Zulu nationalism and racial tensions in South Africa. On the other fore, riots that occurred in both KwaZulu-Natal and Gauteng were accompanied by criminality such as: lootings, torching and burning of private and public properties and to a larger degree, murder of civilians. Findings are that, urban riots in both Gauteng and KwaZulu-Natal provinces have resulted into human (in) securities such as exacerbation of poverty, food and fuel shortages, effects on the health sector (amidst Covid-19 crisis), loss of lives, and an increase in unemployment. Methodologically, the study relies on mixed method of research and content analysis.